To have and to hold an intimate history of collectors and collecting - Blom, Philipp 1970- (Penguin Books, 2003)
"Investigating the history of collecting from the Renaissance to our day. Blom shows a multiplicity of worlds: the scientific cabinets of the fifteenth century and an Italian scholar employed as dragon slayer; the 'Ark' of the Tradescants and a friend's betrayal; Emperor Rudolf II's Prague collection as 'practised alchemy': the macabre art of Dr. Frederik Ruysch, first among embalmers; and the overflowing menagerie of Sir Hans Sloane's curiosities, later to become the foundation of the British Museum. He also discusses the strange fate of Angelo Soliman, a black man at the Habsburg court who was stuffed and exhibited with wild animals; explores the rise of scientific collecting and classification and, parallel to it, the explosion of collecting as the private passion of hundreds of thousands; and introduces Robert Opie, whose collection of half a million items of household packaging now fills his home in London and two overloaded warehouses in Gloucestershire besides." "Out of this glittering diversity of material Blom distils the themes underlying this seemingly elusive pursuit: conquest and possession, and the awareness of our own mortality."--Jacket.